Opioid use disorder in primary care: PEER umbrella systematic review of systematic reviews - Korownyk, Christina (Can Fam Physician, 2019)
OBJECTIVE: To summarize the best available evidence regarding various topics related to primary care management of opioid use disorder (OUD). DATA SOURCES: MEDLINE, Cochrane Library, Google, and the references of included studies and relevant guidelines. STUDY SELECTION: Published systematic reviews and newer randomized controlled trials from the past 5 to 10 years that investigated patient-oriented outcomes related to managing OUD in primary care, diagnosis, pharmacotherapies (including buprenorphine, methadone, and naltrexone), tapering strategies, psychosocial interventions, prescribing practices, and management of comorbidities. SYNTHESIS: From 8626 articles, 39 systematic reviews and an additional 26 randomized controlled trials were included. New meta-analyses were performed where possible. One cohort study suggests 1 case-finding tool might be reasonable to assist with diagnosis (positive likelihood ratio of 10.3). Meta-analysis demonstrated that retention in treatment improves when buprenorphine or methadone are used (64% to 73% vs 22% to 39% for control), when OUD is treated in primary care (86% vs 67% in specialty care, risk ratio [RR] of 1.25, 95% CI 1.07 to 1.47), and when counseling is added to pharmacotherapy (74% vs 62% for controls, RR = 1.20, 95% CI 1.06 to 1.36). Retention was also improved with naltrexone (33% vs 25% for controls, RR = 1.35, 95% CI 1.11 to 1.64) and reduced with medication-related contingency management (eg, loss of take-home doses as a punitive measure; 68% vs 77% for no contingency, RR = 0.86, 95% CI 0.76 to 0.99). CONCLUSION: There is reasonable evidence that patients with OUD should be managed in the primary care setting. Diagnostic criteria for OUD remain elusive, with 1 reasonable case-finding tool. Methadone and buprenorphine improve treatment retention, while medication-related contingency methods could worsen retention. Counseling is beneficial when added to pharmacotherapy.